Dimensi-Dimensi Pendidikan Islam dalam Perspektif QS Surat As Sajdah Ayat 7-9 - Ahmad Yusuf (Institut Agama Islam Negeri Palopo, 2021)
AbstractAllah created everything in a perfect form according to its duties and functions. Likewise, humans are the most perfect creatures among other creatures. That is why humans carry out their duties as caliphs on earth. In order to carry out their roles and functions properly, humans cannot be separated from education. Islamic education is plays a very important role in equipping humans. The purpose of writing this article is to explore and describe the contextualization of the Al Qur'an Surat As Sajdah verses 7-9 in the Process of Islamic Education. The results of this study are: 1) Q.S. As Sajdah Verses 7-9 are the basis for refuting Darwin's theory which states that humans come from apes. 2) Islamic education in QS As Sajdah Verses 7-9 contains the main meaning, namely; confession of faith in Allah SWT, paying attention to the basic components of education, using a systematic-pragmatic method, 3). Education and learning will get optimal results if optimizing the potential of the human senses in the form of hearing, sight and reason (heart), 4) Al Qur'an surah As Sajdah verses 7-9 in Islamic education can be understood from various points of view, namely physiological, psychological, and theology and sociology of education as well as an open attitude and receiving information from various sciences can minimize the dichotomy of knowledge and give birth to educated people with multidisciplinary abilities Keywords: Humans, Education, Q.S As Sajdah, Potential Sense AbstrakAllah menciptakan segala sesuatu dalam bentuk yang sempurna sesuai dengan tugas dan fungsinya. Begitupun manusia menjadi makhluk paling sempurna di antara makhluk yang lain. Oleh karena itulah manusia mengemban tugas sebagai khalifah di bumi. Agar dapat menjalankan peran dan fungsinya dengan baik, manusia tidak bisa terlepas dari pendidikan. PendidikanIslam sangat berperan dalam membekali manusia. Tujuan penulisan artikel ini adalah untuk menggali dan mendeskripsikan kontekstualisasi Al Qur’an Surat As Sajdah ayat7-9 dalam Proses Pendidian Agama Islam. Hasil dari penelitian ini yaitu: 1) Q.S. As Sajdah Ayat 7-9 ini sebagai dasar yang membantah teori Darwin yang menyebutkan manusia berasal dari kera, 2) Pendidikan Islam dalam QS As Sajdah Ayat 7-9 mengandung makna utama yairtu; pengakuan keimanan kepada Allah SWT, memperhatikan komponen-komponen dasar pndidikan, menggunakan metode yang sistematis-pragmatis, 3). Pendidikan dan pembelajaran akan optimal memperoleh hasil jika mengoptimalkan potensi indera manusia berupa pendengaran, penglihatan dan akal(hati), 4) Al Qur’an surat As Sajdah ayat 7-9 dalam pendidikan Islam dapat difahami dari berbagai sudut pandang yaitu dimensi fisiologis, psikologis, teologis dan sosiologi pendidikan serta sikap terbuka dan menerima informasi dari berbagai ilmu dapat meminimlaisir dikotomi ilmu dan melahirkan orang-orang yang terdidik dengan kemampuan multidisiplin Kata Kunci: Manusia, Pendidikan, Q.S As Sajdah, Potensi Indera